Efficacy and safety of endoscopic submucosal dissection using a scissors‐type knife with prophylactic over‐the‐scope clip closure for superficial non‐ampullary duodenal epithelial tumors. Issue 6 (5th February 2020) - Dohi, Osamu; Yoshida, Naohisa; Naito, Yuji; Yoshida, Takuma; Ishida, Tsugitaka; Azuma, Yuka; Kitae, Hiroaki; Matsumura, Shinya; Takayama, Shun; Ogita, Kazuyuki; Mizuno, Naoki; Nakano, Takahiro; et al.
Abstract : Background and study aim: This study aimed to assess the safety and feasibility of endoscopic submucosal dissection (ESD) using a scissors‐type knife with prophylactic closure using over‐the‐scope clip (OTSC) for superficial non‐ampullary duodenal epithelial tumors (SNADETs). Patients and methods: Consecutive patients who underwent ESD for SNADETs >10 mm between January 2009 and July 2019 were retrospectively enrolled. We performed ESD using either a needle‐type knife (Flush Knife‐ESD) or a scissors‐type knife (Clutch Cutter‐ESD). Mucosal defects were prophylactically closed using three methods: conventional clip, laparoscopic closure, or OTSC. Results: A total of 84 lesions were resected using the Flush Knife‐ESD and the Clutch Cutter‐ESD (37 and 47 patients, respectively), and conventional clip, laparoscopic closure, and OTSC for mucosal defect closure after ESD were applied in 13, 13, and 56 lesions, respectively. The R0 resection rate was significantly higher in the Clutch Cutter‐ESD than that in the Flush Knife‐ESD (97.9% vs 83.8%, respectively, P  = 0.040). The intraoperative perforation rate was significantly lower in the Clutch Cutter‐ESD than in the Flush Knife‐ESD (0% vs 13.5%, respectively, P  = 0.014). Complete closure rates of conventional clip, laparoscopic closure, and OTSC were 76.9%, 92.3%, and 98.2%, respectively ( P  = 0.021); and delayed perforation rates were 15.4%, 7.7%, and 1.8%, respectively ( P  = 0.092). Conclusions: Endoscopic submucosal dissection using a scissors‐type knife with prophylactic OTSC closure is safe and feasible for the low‐invasive treatment of SNADETs.